ДОСЛІДЖЕННЯ МОЖЛИВОСТІ ПЕРЕВЕДЕННЯ МІЖДЕРЖАВНОЇ ЕЛЕКТРОПЕРЕДАЧІ ЗАХІДНОУКРАЇНСЬКА-САБОЛЧБАКА НА НОМІНАЛЬНУ НАПРУГУ 400 КВ - Кацадзе, Т.Л.; Лугін, Д.М. (Інститут електродинаміки Національної академії наук України, 2026)
The article discusses the technical and energy feasibility of converting the inter-state overhead power line Zakhidnoukrainska – Szabolcsbaka from a nominal voltage of 750 kV to 400 kV within the dimensions of the existing line. The relevance of the study is determined by the need to improve the efficiency of the unified energy system of Ukraine, strengthen its stability, and integrate it with the energy market of the European Union. One of the key elements of the interstate energy intersection is the 750 kV Zakhidnoukrainska – Szabolcsbaka line, whose operating modes are characterized by significant power losses due to corona discharge. The paper presents the results of modeling the Ukraine-Hungary transit operating modes, performed in the PowerFactory software environment for two line operation options – at 750 kV and 400 kV. A comparative analysis of active power losses (Joule losses and corona losses) was performed, taking into account the influence of weather conditions (clear weather, rain, snow, frost) and different load levels. The calculations showed that at a voltage of 750 kV, corona discharge losses prevail over Joule losses, especially in unfavorable weather conditions, while in the 400 kV option, the share of corona losses is significantly reduced, but Joule losses increase. It has been established that reducing the nominal voltage to 400 kV is energy efficient only at relatively low line loads – up to 200 MW in clear weather, up to 400 MW during snow, 750 MW during rain, and 950 MW during frost. For larger power flows, it is advisable to maintain a voltage of 750 kV, as the total losses are lower in this case. Ref. 10, fig. 6, tables 4.